1989
DOI: 10.1111/j.1365-2265.1989.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Hypertension

Abstract: The importance of changes in hormone secretion in human hypertension is a complex problem and too large to be dealt with in uniform detail in a short review. The subject encompasses not only the effects on blood pressure of primary endocrine disorders but also hormonal changes secondary to increased blood pressure. Some aspects are more fully understood than others and have been the subjects of relatively recent detailed reviews. Where this is the case, the current review has summarized the present position an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 284 publications
2
35
0
Order By: Relevance
“…Both aldosterone and cortisol (or corticosterone) have important effects on electrolyte balance and blood pressure by their actions on the kidney and the vasculature (Fraser et al 1989). In addition to these systemic effects, however, it is clear that they exert significant central effects.…”
Section: -Hydroxylase Is Localised In the Zona Fasciculata And Is Regmentioning
confidence: 99%
“…Both aldosterone and cortisol (or corticosterone) have important effects on electrolyte balance and blood pressure by their actions on the kidney and the vasculature (Fraser et al 1989). In addition to these systemic effects, however, it is clear that they exert significant central effects.…”
Section: -Hydroxylase Is Localised In the Zona Fasciculata And Is Regmentioning
confidence: 99%
“…increased gluconeogenesis, insulin resistance, and lipolysis), glucocorticoids have a role in the complex interplay between pro-and anti-inflammatory pathways (1) and exert multiple vascular effects. Glucocorticoids increase blood pressure by enhancing sensitivity of vascular smooth muscle to catecholamines and angiotensin II, by increasing angiotensinogen synthesis, by reducing nitric oxidemediated endothelial dilatation and by sodium retention in the distal nephron (2,3). Consequently, chronic exposure to high doses of endogenous or exogenous glucocorticoids often results in an unfavorable metabolic profile and cardiovascular disease (CVD) (4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In patient #1 this central response to aldosterone could have been modified by long-term treatment with glucocorticoids, although prednisone, used in this patient, has a very low affinity for MR (22). Moreover, excess glucocorticoids usually have a hypertensive action (23). DXM-sensitive hyperaldosteronism was also considered in both patients because recent data have shown that carriers of chimerism of the 11-beta-hydroxylase/ aldosterone synthase gene have a broad range of phenotypes and do not necessarily have arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%